Kemampuan Bermedia dan Daya Kritis Para Mahasiswa Di Kabupaten Manggarai - Flores - Marianus Mantovanny Tapung; Ambros Leonangung Edu; Petrus Redy Partus Jaya (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2019)
Abstract:This study aims to describe the ability of media and the critical power of students in Manggarai Regency. The ability to media is measured by indicators: The types of social media that are most often used, the ability to apply social media, frequently sought media content, the critical power of social media content, and social media content that is often distributed. The type of research used was a descriptive cross sectional study. The research respondents were 353 students who were determined using the proportional stratified random sampling technique. Data was collected using an online questionnaire. To guarantee the credibility of the data, researchers applied the one vote method and cross-checked through interviews via mobile phones. Data is presented in the form of tables and graphs. The results of the study show that the types of media most used by students are Facebook and WhatsApp. Both types of social media are applied by students themselves. Most students are able to apply these social media proficiently. However, many students use the media to access content that does not support their intellectual knowledge and insight. The use of media is limited to building social relations or friendship among students. This habit has an impact on students' critical power in assessing hoax content and factual content. The results of this study illustrate the discrepancy between the ability to apply media and students' critical power. This condition must be the concern of educators and stakeholders in Manggarai Regency.Keywords: Media, Critical Power, Manggarai Flores Students Abstrak:Penelitian ini bertujuan mendeskripsikan kemampuan bermedia dan daya kritis mahasiswa di Kabupaten Manggarai. Kemampuan bermedia diukur berdasarkan indikator-indikator: Jenis media sosial yang paling sering digunakan, kemampuan mengaplikasikan media sosial, konten media yang sering dicari, daya kritis terhadap konten media sosial, dan konten media sosial yang sering disebarkan. Jenis penelitian yang digunakan adalah penelitian deskriptif cross sectional. Responden penelitian berjumlah 353 mahasiswa yang ditentukan menggunakan teknik proportional stratified random sampling. Data dikumpulkan menggunakan kuesioner online. Untuk menjamin kredibilitas data, peneliti menerapkan metode one vote dan melakukan crosscheck melalui wawancara via handphone. Data disajikan dalam bentuk tabel dan grafik. Hasil penelitian menunjukkan bahwa jenis media yang paling banyak digunakan mahasiswa adalah facebook dan whatsapp. Kedua jenis media sosial ini diaplikasikan sendiri oleh mahasiswa. Sebagian besar mahasiswa mampu mengaplikasikan media-media sosial tersebut secara mahir. Namun, banyak mahasiswa menggunakan media untuk mengakses konten-konten yang kurang mendukung pengetahuan dan wawasan intelektual mereka. Penggunaan media hanya sebatas membangun relasi sosial atau pertemanan di antara mahasiswa. Kebiasaan ini berdampak pada daya kritis mahasiswa dalam menilai konten-konten hoax dan konten-konten fakta. Hasil penelitian ini menggambarkan adanya diskrepansi antara kemampuan mengaplikasikan media dengan daya kritis mahasiswa. Kondisi ini mesti menjadi perhatian para pendidik dan stakeholdersdi Kabupaten Manggarai.Kata Kunci: Media, Daya Kritis, Mahasiswa Manggarai Flores